Aplicação móvel de pagamento e validação para Transportes Públicos de Passageiros - André Gonçalves Dias (2013)
The use of mobile devices is more and more a daily routine in human beings. Mobile phones, .mp3 players, tablets, GPS, cameras, etc. are now ordinary objects in pockets or bags. It's precisely due to the capacities of smartphones, the smart mobile phones that revolutionized the way mobile phones are seen, no longer being just a tool to make calls and send text messages, and becoming a complete system of diary, phone, multimedia player, camera, GPS navigator, among others, that arises the question: "If smartphones support all these functionalities, why not use it on one daily task for most people, public transportation?".Although, in Portugal, the use of computerized and relatively sophisticated systems in public transportation ticketing is now a common practice, it is still "stuck" to cards. In Oporto, there is the Andante card, in Lisbon the Viva card and in trains, the CP card. Is the stored information so complex that it couldn't be stored anywhere else, for instance in a smartphone? The answer is obvious, No! The stored information is only the number of remaining traveling titles in that card, and in case one title is active, the expiration time and departure station. All this information can be easily stored in a smartphone, with only the need to develop the technological infrastructures to support this model.The aim of this project is precisely to study and conceive the best way to take advantage of smartphones to replace cards in the Oporto Metropolitan Area public transportation system. This would not only increase passenger's commodity but also provide him an unlimited and place and time independent access to all the needed services related to his mobility management. These services include purchasing traveling titles, and validating them, checking the virtual wallet balance and the titles balance, visualizing the operations history, visualizing the status of an active title (remaining time, departure station, number of zones, etc.), among others.But the passenger is not the only one who benefits. The passengers public transportation operators, besides adding value to their services offer, reduce operation and maintenance costs, and gather statistical information and use habits from their customers. Moreover, they show the will to be in the edge of technological innovation. There are already some pilot projects running in different countries, searching for the best solution. It is important to have in mind that each public transportation network is unique and with special characteristics, so it will never be possible to find a general solution that fits every model, enforcing the necessity to develop an appropriate solution for each network.Not only the mobile ticketing system for the Oporto Metropolitan Area was developed but also tested with real users. The feedback they gave was important to identify problems and improvement suggestions and also to test the concept of buying and validating tickets by mobile phone.